Learning Android forensics : a hands-on guide to Android forensics, from setting up the forensic workstation to analyzing key forensic artifacts /: a hands-on guide to Android forensics, from setting up the forensic workstation to analyzing key forensic artifacts. (2015) - Tamma, Rohit; Tindall, Donnie
No abstract available